An Analysis of Lecturers’ Oral Corrective Feedback on EFL Students’ Speaking Performance at One Public University in Jambi - Rilda, Aniza (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Corrective feedback is used as a basis for improvement. Giving corrective feedback plays an important role to encourage students to improve their speaking skills and make them aware of their speaking error. Thus, this qualitative study applied case study approach to explore the types of oral corrective feedback used by lecturers in correcting students’ speaking error in Oracy Class at One Public University in Jambi and their reasons for choosing certain types of oral corrective feedback. The participants of this research were three lecturers who teach Oracy Class. The data were collected through semi-structured interviews and observations with the guidance of interview protocol and observation checklist as the instruments. In this study, it was found that lecturers used oral corrective feedback by giving reformulation through explicit correction and recast and giving prompt through clarification request, metalinguistic feedback, and repetition. Then, their reasons for using certain types of oral corrective feedback were because they were considering the students’ level and skills and preparing the students for global competition. Furthermore, it can be concluded that the lecturers only applied five types of oral corrective feedback proposed by Lyster and Ranta (1997) such as explicit correction, recast, clarification request, metalinguistic feedback and repetition.